1999
DOI: 10.1590/s0074-02761999000500028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environmental temperature on life tables of Rhodnius neivai Lent, 1953 (Hemiptera: Reduviidae) under experimental conditions

Abstract: Changes in life tables of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…Several studies have shown the influence of temperature on the development of triatomines (Juárez & Silva, 1982; Silva, 1988; Cabelo, 1999; Luz et al ., 1999). The environmental temperature affects the fecundity and the maturity rate of T. infestans (Jörg, 1960, 1989) and Mepraia spinolai (Ehrenfeld et al ., 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the influence of temperature on the development of triatomines (Juárez & Silva, 1982; Silva, 1988; Cabelo, 1999; Luz et al ., 1999). The environmental temperature affects the fecundity and the maturity rate of T. infestans (Jörg, 1960, 1989) and Mepraia spinolai (Ehrenfeld et al ., 1998).…”
Section: Discussionmentioning
confidence: 99%
“…En consecuencia, es difícil comparar los resultados sobre ciclos de vida existentes en la literatura, debido a las variaciones experimentales de cada trabajo. Por ejemplo, para algunas especies de Rhodnius se han reportado promedios de 102 y 120 días, como es el caso de R. ecuadoriensis (15); de 101, 127 y 209,4 días para R. nasutus (16,17); de 104, 131, 154,2 y 177,1 días para R. neglectus (18,19); de 181,2, 118, 86,7 y 68,9 días para R. neivai (20,21); de 212 y 126 días para R. pallescens (22); de 190,7, 278 y 118 días para R. pictipes (20,23,24); de 114, 140 y 118 días para R. prolixus (20,25), y de 114 y 135 días para R. robustus (26). En otros géneros de triatominos se han observado promedios de 196,8 y 189,5 días para Meccus picturatus (27); de 230,3 días para Triatoma flavida (28), y de 180,1 días para T. rubrovaria (29).…”
Section: Ciclo De Vidaunclassified
“…Since Rabinovich (1972a) superb paper on Triatoma infestans (Klug), vital statistics under laboratory conditions, the development of biodemographic studies on triatomines has been very prolific and life‐table studies on several species have been carried out ( Rabinovich , 1972b; Rodríguez and Rabinovich , 1980; Zeledón , 1981; Feliciangeli and Rabinovich , 1985; Cabello et al., 1987; Cabello and Galíndez , 1998; Guarneri et al., 1998; Cabello , 1999). The importance of such studies is because they, together with field observations, provide critical information: (i) to design optimal control strategies, (ii) on the population potential growth and its relationship with invasibility, the ability of a species to become established after the introduction of some individuals into a new habitat ( Rabinovich , 1972a; Carey , 1982).…”
Section: Introductionmentioning
confidence: 99%